Pengaruh indeks harga konsumen, tingkat partisipasi angkatan kerja, dan investasi terhadap upah minimum di Provinsi Jambi Tahun 2002-2023 - Panjaitan, Ester; Hari Prihanto, Purwaka; Kusuma Edy, Jaya (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
The purpose of this study was to analyze the development of the Consumer Price Index, Labor Force Participation Rate, Investment and Provincial Minimum Wage and analyze the effect of the Consumer Price Index, Labor Force Participation Rate and Investment on the Jambi Provincial Minimum Wage. The analysis method used is descriptive analysis and quantitative analysis using secondary data. Based on the results of the analysis it can be concluded that during the period 2002 to 2023 the average development of the Consumer Price Index was 2.51%, the average Labor Force Participation Rate was 0.08%, the average investment development was 20.17% and the development of the Provincial Minimum Wage was 11.03%. Simultaneously the Consumer Price Index, Labor Force Participation Rate and Investment have a significant effect on the Provincial Minimum Wage. Partially, the Labor Force Participation Rate has no effect on the Provincial Minimum Wage, while the Consumer Price Index and investment have an effect on the Provincial Minimum Wage.